Nonviable mutants of simian virus 40 with deletions near the 3' end of gene A define a function for large T antigen required after onset of viral DNA replication. - Tornow, J (1983)
Deletion mutants of simian virus 40 (SV40) with lesions at the three DdeI sites near the 3' end of the early region were constructed. Mutants with deletions at 0.203 and 0.219 map units (mu) which did not change the large T antigen reading frame were viable. This extends slightly the upstream boundary for the location of viable mutants with deletions in the 3' end of the A gene. Mutants with frameshift deletions at 0.193 and 0.219 mu were nonviable. These are the first nonviable mutants with deletions in this portion of the A gene. None of the three nonviable mutants with deletions at 0.219 mu produced progeny viral DNA. These three mutants all used the alternate reading frame located in this portion of the SV40 early region. The mutant with a deletion at 0.193 mu, dlA2459, was positive for viral DNA replication and was defective for adenovirus helper function. All of these mutations were located in the portion of the SV40 large T antigen which has no homology to the polyoma T antigens. These results indicate that this portion of large T antigen is required for some late step in the viral growth cycle and suggest that adenovirus helper function is required for productive infection by SV40.